Palladium-doped polystyrene nanoplastic with core-shell structure and preparation method thereof
By preparing palladium-doped nanoplastics with core-shell structures in polystyrene nanoplastics, the problem of insufficient particle size and uniformity of nanoplastics in the prior art is solved, a smaller and uniform particle size is achieved, and the stable existence of metal elements is ensured, and the application prospects of nanoplastics are significantly improved.
Patent Information
- Application Number
- CN202310053844.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-02-03
AI Technical Summary
The existing metal-doped nanoplastics have shortcomings in particle size and uniformity, and the metal elements are large on the surface or particle size of the nanoplastics, resulting in difficulty in quantitative detection and increased ecological risks.
The preparation method of palladium-doped polystyrene nanoplastics with core-shell structure is adopted to ensure that the metal element Pd exists stably in the core of the nanoplastics by controlling the reaction conditions and material usage, and a smaller and uniform particle size is achieved through gradient transitions.
Accurate quantity detection of nanoplastics is achieved, avoiding the leakage of metal elements, ensuring that the particle size of nanoplastics is about 100nm, the size is more uniform, and the surface is smoother, which significantly improves the application prospects of nanoplastics.
Smart Images

Figure CN115960318B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a palladium-doped polystyrene nanoplastic with a core-shell structure and a preparation method thereof, belonging to the technical field of material synthesis. Background Art
[0002] As the production of plastic products increases year by year, the amount of plastic waste discharged into the environment is increasing dramatically. Under the influence of physical, chemical, biological and other factors, plastics are decomposed into smaller microplastics and even nanoplastics. Nanoplastics (particle size ≤ 100nm) in the environment are very easy to migrate due to their small size, and their surfaces are very easy to adsorb other pollutants in the environment, such as persistent organic pollutants and heavy metals. At the same time, nanoplastics will spread along the food chain, thereby causing adverse effects on the growth, development and reproduction of organisms, and ultimately posing a threat to human health. Therefore, the behavior of nanoplastics in the environment and their ecological risks have become a research hotspot in recent years.
[0003] Due to the small particle size of nanoplastics and the limitations of analytical methods and instruments, it is still very difficult to study the behavior and ecological risks of nanoplastics in the environment. However, in laboratory studies that simulate natural environments, improvements in the preparation process of nanoplastics can greatly solve the current research bottleneck.
[0004] In recent years, the use of rare metal-doped nanoplastics to study their environmental behavior and ecological health risks has become an important means, which has achieved convenient and accurate quantitative detection of nanoplastics in complex media. However, the metal-doped nanoplastics prepared in the prior art still have certain problems, such as leakage of doped metal elements, doped metals on the surface of nanoplastics, large and uneven particle size, etc. Therefore, it is necessary to optimize the preparation process of metal-doped nanoplastics so that they have smaller and more uniform particle sizes and the metal elements are stably present in the nanoplastic core. Summary of the invention
[0005] In view of the above prior art, the present invention provides a palladium-doped polystyrene nanoplastic with a core-shell structure and a preparation method thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing palladium-doped polystyrene nanoplastics having a core-shell structure comprises the following steps:
[0008] (I) Preparation of core
[0009] (1) mixing a surfactant, sodium dodecyl sulfate (SDS), acrylonitrile (AN), an initiator, potassium persulfate (KPS), and water (60° C.) in a reaction vessel to form a polymer colloid, filling the reaction vessel with an inert gas (such as nitrogen) to ensure that the air in the reaction vessel is completely exhausted, and sealing the reaction vessel;
[0010] The amount of SDS is 2% to 5% of AN (weight percentage, the same below), preferably 3%; the amount of KPS is 2% to 5% of AN, preferably 3%; the amount of water is 8 to 10 times (weight ratio) of AN, preferably 9 times;
[0011] (2) adding an additional initiator, potassium poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether (KPE) or a solution thereof, and a metal precursor, potassium tetrachloropalladate (K2PdCl4) or a solution thereof, simultaneously within 2 minutes to allow the metal element to combine with the polymer colloid and ensure that the polymer colloid is in a stable state;
[0012] The amount of KPE is 1% to 3% of AN, preferably 2%; the amount of K2PdCl4 is 1% to 2% of AN, preferably 1.5%;
[0013] Further, the concentration of the KPE solution is 30 mg / ml; the concentration of the K2PdCl4 solution is 22.5 mg / ml;
[0014] (3) continuing the reaction in an oil bath at 55 to 65° C. for 38 to 42 minutes;
[0015] (II) Shell preparation
[0016] (4) Styrene, AN and water are mixed in a feeder 1, wherein the weight ratio of styrene, AN and water is 1-2:30-35:65-70, preferably 1.3:33.7:66;
[0017] Further, the amounts of styrene, AN and water are 1.3%, 33.7% and 66% of the total weight of AN and water in step (i) (1), respectively;
[0018] (5) Styrene, SDS, divinylbenzene (DVB) and water are mixed in a feeder 2, wherein the weight ratio of styrene, DVB and water is 1-2:1.5-2.0:60-70, preferably 1.3; 1.7:66; the amount of SDS is 14%-17% of the weight of styrene in step (ii) (4), preferably 15.5%;
[0019] Furthermore, the amounts of styrene, DVB and water are 1.3%, 1.7% and 66% of the total weight of AN and water in step (i) (1), respectively; the amount of SDS is 15.5% of the weight of styrene in step (ii) (4);
[0020] (6) adding additional initiator KPS or its solution to the reaction vessel, wherein the amount of KPS added is 1% to 2%, preferably 1.5%, of AN in step (i) (1);
[0021] Further, the concentration of the KPS solution is 45 mg / ml;
[0022] (7) allowing the solution in feeder 2 to continuously flow into feeder 1, and at the same time allowing the solution in feeder 1 to continuously flow into the reaction vessel, and continuing the reaction for 1.5 to 2.5 hours, preferably 2 hours, to achieve a gradient transition from the core material acrylonitrile to the shell styrene; during the entire reaction process, the feed amount of feeder 1 (referring to the total weight of the material entering feeder 1 from feeder 2, to the total weight of the initial material in the reaction vessel) is 17% to 25%, preferably 20%; the feed amount of the reaction vessel (referring to the total weight of the material entering the reaction vessel from feeder 1, to the total weight of the initial material in the reaction vessel) is 17% to 25%, preferably 20%;
[0023] (8) Remove feeder 1 and allow the solution in feeder 2 to flow directly into the reaction vessel to ensure that only styrene is located in the outermost layer of the nanoplastic. Continue the reaction for 25 to 35 minutes, preferably 30 minutes; the feed amount of the reaction vessel (referring to the total weight of the material entering the reaction vessel from feeder 2, to the total weight of the initial material in the reaction vessel) is 4% to 8%, preferably 5%;
[0024] (9) removing the feeder 2 and allowing the solution in the reaction vessel to react alone for 1.5 to 2.5 hours, preferably 2 hours;
[0025] (10) adding an appropriate amount of water to prevent agglomeration of the polymers, and continuing the reaction for 8 to 12 minutes, preferably 10 minutes;
[0026] (III) Cleaning
[0027] (11) The solution after the reaction is washed with anhydrous ethanol for several times (3 to 6 times) to fully wash away the excess organic matter and surfactant on the surface of the nanoplastic;
[0028] (12) The final precipitate was resuspended in water, placed in a dialysis bag, and dialyzed in water to wash away the residual ethanol for 3 days, with the water replaced every 24 hours. After dialysis, the resulting solution was a solution of palladium-doped polystyrene nanoplastics with a core-shell structure, which was transferred to a glass container and stored at room temperature.
[0029] The palladium-doped polystyrene nanoplastic with a core-shell structure prepared by the above method achieves accurate quantification of nanoplastics and can be used to explore the environmental behavior, ecotoxicology, and ecological effects of nanoplastics in the natural environment.
[0030] The palladium-doped polystyrene nanoplastic with a core-shell structure prepared by the above method, the metal element Pd is doped in the core, which not only retains the original chemical properties of the nanoplastic, but also avoids the problem of metal element leakage in the nanoplastic, making the quantification of the nanoplastic more accurate. The preparation method of the present invention controls the synthesis time, material dosage, flow rate and other conditions, so that the particle size of the synthesized nanoplastic is about 100nm, the size is more uniform, and the surface is smoother, achieving a nano-level breakthrough in the synthetic particle size of the core-shell structure metal-doped nanoplastic (the particle size of the nanoplastic prepared in the prior art is at least about 200nm, and the size is uneven, reference: Mitrano, DM, Beltzung, A., Frehland, S., Schmiedgruber, M., Cingolani, A., & Schmidt, F. (2019). Synthesis of metal-doped nanoplastics and their utility to investigate fate and behavior in complex environmental systems. Nature nanotechnology, 14 (4), 362-368.). The invention also thoroughly cleans the nanoplastics, avoiding interference of organic matter or surfactants remaining on the surface of the nanoplastics on subsequent research. The palladium-doped polystyrene nanoplastics with a core-shell structure of the invention have good application prospects. The invention is of great significance for studying the environmental fate and ecological health risks of nanoplastics. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : Schematic diagram of the reaction apparatus.
[0032] Figure 2 : Scanning electron microscope (SEM) morphology characterization of nanoplastics.
[0033] Figure 3 : Energy spectrum (EDS) element distribution diagram of nanoplastics, where, from top to bottom and from left to right, they are the original SEM image of the nanoplastics, the distribution diagrams of N+C+O+Pd, C, O, N, and Pd.
[0034] Figure 4 : Fourier transform infrared spectrum (FTIR) of nanoplastics.
[0035] Figure 5 : Hydrophilicity and hydrophobicity diagram of nanoplastics, where the n-octanol / water partition coefficient (Kow) is 0.186. Compounds with lower Kow values (<10) can be considered to be more hydrophilic; if the compound has a higher Kow value (>10), it can be considered to be hydrophobic.
[0036] Figure 6 : Schematic diagram of the detection limit of palladium concentration in nanoplastics.
[0037] Figure 7 : Schematic diagram of the particle number detection limit of nanoplastics. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the embodiments. However, the scope of the present invention is not limited to the following embodiments. It will be appreciated by those skilled in the art that various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention.
[0039] The instruments, reagents, materials, etc. involved in the following embodiments, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.
[0040] Example 1 Preparation of palladium-doped polystyrene nanoplastics with core-shell structure
[0041] The reaction apparatus used is as follows Figure 1 As shown, it includes a three-necked flask, a feeder 1 and a feeder 2 which are connected in sequence by a peristaltic pump, wherein the three-necked flask is placed in an oil bath, a magnetic stirrer is placed in the three-necked flask, and a magnetic stirrer is placed at the bottom of the oil bath; magnetic stirrers are placed in feeders 1 and 2, and a magnetic stirrer is placed at the bottom.
[0042] Here are the steps:
[0043] (I) Preparation of core
[0044] (1) 108 ml of 60° C. water was placed in a three-necked flask, and 0.36 g of a surfactant, sodium dodecyl sulfate (SDS), 12 g of acrylonitrile (AN), and 0.36 g of an initiator, potassium persulfate (KPS), were added under stirring (300 rpm) to form a polymer colloid, and nitrogen was introduced to ensure that the air in the three-necked flask was completely discharged, and the flask mouth was sealed;
[0045] (2) within 2 minutes, 8 ml of an initiator potassium poly(ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether (KPE) solution (containing 0.24 g of KPE, the concentration of the KPE solution is 30 mg / ml) and 8 ml of a metal precursor potassium tetrachloropalladate (K2PdCl4) solution (containing 0.18 g of K2PdCl4, the concentration of the K2PdCl4 solution is 22.5 mg / ml) are added simultaneously with a syringe to allow the metal element to combine with the polymer colloid and ensure that the polymer colloid is in a stable state;
[0046] (3) The reaction was continued in an oil bath at 60°C for 40 minutes;
[0047] (II) Shell preparation
[0048] (4) Mix 1.56 g styrene, 40.44 g AN and 79.2 ml water in feeder 1 and continue stirring to ensure thorough mixing;
[0049] (5) 1.56 g styrene, 0.2418 g SDS, 2.04 g divinylbenzene (DVB) and 79.2 ml water were mixed in feeder 2 and stirred continuously to ensure thorough mixing;
[0050] (6) 4 ml of additional initiator KPS solution (containing 0.18 g of KPE, the concentration of KPS solution is 45 mg / ml) is added to the three-necked flask via a syringe;
[0051] (7) The solution in feeder 2 flows into feeder 1, and the solution in feeder 1 flows into the three-necked flask at a flow rate of 200 μl / min. The reaction is continued for 2 hours to achieve a gradient transition from acrylonitrile as the core material to styrene as the shell material.
[0052] (8) Remove feeder 1 and allow the solution in feeder 2 to flow directly into the three-necked flask at the same flow rate (200 μl / min) to ensure that only styrene is located in the outermost layer of the nanoplastic. Continue the reaction for 0.5 h.
[0053] (9) Remove feeder 2 and allow the solution in the three-necked flask to react alone for 2 hours;
[0054] (10) Add an appropriate amount of water (20 g) to the three-necked flask to prevent agglomeration of the polymers, and continue the reaction for 10 minutes. After the reaction is completed, remove the three-necked flask from the oil bath, transfer the solution to a glass bottle, and store at room temperature.
[0055] (III) Cleaning
[0056] (11) The reaction solution in the three-necked flask was mixed with anhydrous ethanol at a volume ratio of 1:1 and centrifuged (5000 rpm for 10 min); the supernatant was removed, and the precipitate was resuspended in anhydrous ethanol and centrifuged (under the same conditions as above); this process was repeated 5 times to fully wash away the excess organic matter and surfactant on the surface of the nanoplastic;
[0057] (12) The final precipitate was resuspended in water, placed in a dialysis bag, and dialyzed in water to wash away the residual ethanol for 3 days, with the water replaced every 24 hours; after dialysis, the resulting solution was a solution of palladium-doped polystyrene nanoplastics having a core-shell structure (about 200 mL of solution was obtained, the nanoplastic concentration was about 50 g / L, and the mass ratio of Pd element in the core to the plastic ball was 0.29%), which was transferred to a glass container and stored at room temperature.
[0058] The morphology of nanoplastics was observed under a scanning electron microscope (SEM). Figure 2 As shown in the figure, it can be seen that the shape of the nanoplastic is a regular sphere, the particle size is about 100nm, the particle size is uniform, and the surface is relatively smooth.
[0059] Energy dispersive spectrometry (EDS) element distribution of nanoplastics Figure 3 As shown in the figure, it can be seen that the metal element Pd is concentrated in the center of a single nanoplastic ball, meeting the requirement that the metal element is located in the nanoplastic core.
[0060] The Fourier transform infrared spectrum (FTIR) of nanoplastics is shown below: Figure 4 As shown in the figure, it can be seen that the infrared spectrum of the surface of the synthetic nanoplastic is consistent with the infrared characteristic peak of polystyrene, which meets the requirement that the synthesized nanoplastic is polystyrene.
[0061] The solution of the palladium-doped polystyrene nanoplastic with a core-shell structure prepared above was diluted with water to a concentration of 5 g / L, 0.5 ml was taken and added to octanol-saturated water to make the total volume 5 mL, and an equal volume of n-octanol was added to the experimental group. It was placed in a shock box and shaken for 24 hours, then taken out and allowed to stand. The upper n-octanol in the experimental group was sucked out, and the concentration of Pd in the aqueous phase of the control group and the experimental group was measured by inductively coupled plasma mass spectrometry (ICP-MS), and then the octanol-water partition coefficient (Kow) of the synthesized nanoplastic was calculated. The hydrophilicity and hydrophobicity results are shown in FIG. Figure 5 As shown in the figure, it can be seen that the synthetic nanoplastics are mainly distributed in the water phase. Calculations show that the nanoplastics have strong hydrophilicity.
[0062] The synthesized nanoplastics were used to prepare nanoplastic solutions with a certain concentration gradient. After digestion, the concentration of Pd element corresponding to the nanoplastic solutions with different concentrations was determined using ICP-MS, and a linear relationship diagram between nanoplastic concentration and Pd concentration was drawn ( Figure 6 At the same time, after the prepared nanoplastic solution with a certain concentration gradient is fully ultrasonically dispersed, the number of particles is directly measured using ICP-MS, and a linear relationship diagram between nanoplastic concentration and nanoplastic particle number concentration is drawn ( Figure 7 ). The result is Figure 6 , Figure 7 The results showed that the palladium element in the synthetic nanoplastics could be well detected by inductively coupled plasma mass spectrometry (ICP-MS), and the minimum concentration detection limit of nanoplastics was 100 μg / L, and the minimum particle number detection limit was 1 μg / L.
[0063] The above examples are provided to those skilled in the art to fully disclose and describe how to make and use the claimed embodiments, and are not intended to limit the scope of the disclosure herein. Modifications that are obvious to those skilled in the art will fall within the scope of the appended claims.
Claims
1. A method for preparing palladium-doped polystyrene nanoplastics having a core-shell structure, characterized in that: Here are the steps:
1. Preparation of core (1) Place 108 ml of 60°C water in a three-necked flask, add 0.36 g of surfactant sodium dodecyl sulfate, 12 g of acrylonitrile, and 0.36 g of initiator potassium persulfate under stirring at 300 rpm to form a polymer colloid, fill with nitrogen to ensure that the air in the three-necked flask is completely exhausted, and seal the flask mouth; (2) Within 2 minutes, use a syringe to simultaneously add 8 ml of the initiator poly (ethylene glycol) 4-nonylphenyl 3-sulfopropyl ether potassium solution and 8 ml of the metal precursor potassium tetrachloropalladate solution to allow the metal element to combine with the polymer colloid and ensure that the polymer colloid is in a stable state; the concentration of the KPE solution is 30 mg / ml; the concentration of the K2PdCl4 solution is 22.5 mg / ml; (3) Continue the reaction in an oil bath at 60°C for 40 minutes; (II) Shell preparation (4) Mix 1.56 g styrene, 40.44 g AN, and 79.2 ml water in feeder 1 and stir continuously to ensure thorough mixing; (5) Mix 1.56 g styrene, 0.2418 g SDS, 2.04 g divinylbenzene and 79.2 ml water in feeder 2 and stir continuously to ensure thorough mixing; (6) Add 4 ml of additional initiator KPS solution into the three-necked flask via syringe; the concentration of KPS solution is 45 mg / ml; (7) The solution in feeder 2 is allowed to flow into feeder 1, and the solution in feeder 1 is allowed to flow into the three-necked flask at a flow rate of 200 μl / min. The reaction is continued for 2 hours to achieve a gradient transition from acrylonitrile as the core material to styrene as the shell material. (8) Remove feeder 1 and allow the solution in feeder 2 to flow directly into the three-necked flask at a flow rate of 200 μl / min to ensure that only styrene is located in the outermost layer of the nanoplastic. Continue the reaction for 0.5 h. (9) Remove feeder 2 and allow the solution in the three-necked flask to react alone for 2 hours; (10) Add 20 g of water to the three-necked flask to prevent polymer agglomeration, and continue the reaction for 10 minutes. After the reaction is completed, remove the three-necked flask from the oil bath, transfer the solution to a glass bottle, and store at room temperature. (III) Cleaning (11) The reaction solution in the three-necked flask was mixed with anhydrous ethanol at a volume ratio of 1:1 and centrifuged at 5000 rpm for 10 min. The supernatant was removed and the precipitate was resuspended in anhydrous ethanol and centrifuged at 5000 rpm for 10 min. This process was repeated 5 times to fully wash away the excess organic matter and surfactant on the surface of the nanoplastic. (12) The precipitate was resuspended in water, placed in a dialysis bag, and dialyzed in water to wash away the residual ethanol for 3 days, with the water replaced every 24 hours. After dialysis, the resulting solution was a solution of palladium-doped polystyrene nanoplastics with a core-shell structure, wherein the concentration of the nanoplastics was 50 g / L, the mass ratio of the Pd element in the core to the nanoplastics was 0.29%, and the shape of the nanoplastics was a regular sphere with a particle size of 100 nm.
2. The nanoplastic prepared by the preparation method according to claim 1.